Metaverse Challenges and Opportunities in the Gospel Message - Ezra Tari (Riwayat: Educational Journal of History and Humanities, 2023)
The metaverse is a new environment in the technology world that offers the same situation as the real world. This world offers meetings without having to face to face. The situation is up-to-date. The Church does not yet have a virtual fellowship format headed for augmented reality. The challenge of this media is the limited signal coverage. The operational cost of procuring equipment to support this service is prohibitive. The researcher used the library study method. This study seeks to explore material related to the metaverse. To delve into the world of the metaverse, its opportunities, and challenges. The Church compiles age-appropriate content but does not omit the message it wants to convey. The Bible can be understood in the local language and culture. The Church Develops an online learning curriculum.